Identification of vegetative heat‐tolerant upland cotton (Gossypium hirsutum L.) germplasm utilizing chlorophyll fluorescence measurement during heat stress. Issue 2 (27th December 2013) - Wu, Tingting; Weaver, David B.; Locy, Robert D.; McElroy, Scott; van, Edzard; Jenkins, J.
Abstract Heat stress adversely affects upland cotton (Gossypium hirsutum L.) production in the United States. Heat tolerance is difficult to determine, especially when yield and fibre quality are the parameters measured in photoperiodic, non‐adapted genotypes. Our objective was to evaluate wild (mostly photoperiodic, non‐adapted) genotypes for vegetative heat tolerance using chlorophyll fluorescence. Parameters were measured in three phases of heat stress assays to select candidate lines for introgression of increased heat tolerance into commercial cotton germplasm. Forty‐four wild accessions were selected from 1762 wild accessions in the USDA germplasm collection using a single‐leaf sample assay (phase I). In the growth chamber, 6‐week‐old cotton plants were subjected to heat stress at 45°C and 80% humidity for 24 h. After heat stress, the mean ΦPSII for the selected accessions was higher than that of a set of randomly chosen accessions and adapted cultivars (phase II). In the field under high temperatures (>35°C), the top nine accessions had higher average ΦPSII than adapted cultivars (phase III). Based on these results, the three‐phased stepwise approach was consistent in identifying putative genetic resources for increased vegetative heat tolerance. Accessions were identified that may have potential as genetic materials for development of adapted heat‐tolerant upland cotton germplasm.